2019
DOI: 10.1186/s40494-019-0291-9
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic observations of paper and parchment: the archaeology of small objects

Abstract: The study of micro-objects, both inorganic and organic, which can be found associated to parchment or cellulose fibres of books and documents, or in the inks and the dirt, accumulated over the centuries between the pages, can unravel important information on the manufacture of the ancient documents, on their past vicissitudes or on the causes of aging and deterioration of the materials they contain. The results of a critical observation of micrometric objects and structures with a diagnostic or archaeological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Characteristic stromatolite and travertine formations are produced by species precipitating calcium carbonate in their sheaths and within colonial mucilage (Komárek et al, 2003). Some fillers in paper manufacture are based on carbonates from natural sources, such as fossil sedimentary rocks (i.e., biomicrite) (Gerteiser and Laufmann, 1989), which can sometimes be recognized in the form of microfossils among the paper fibers (Bicchieri et al, 2019). It is therefore possible to speculate that the presence of cyanobacteria is due to the use of carbonatebased filler material and natural rocks, perhaps from recent sedimentation, in the manufacture -if not of the Leonardo drawing-perhaps of the cartoons supporting the drawing itself.…”
Section: Bacteriamentioning
confidence: 99%
“…Characteristic stromatolite and travertine formations are produced by species precipitating calcium carbonate in their sheaths and within colonial mucilage (Komárek et al, 2003). Some fillers in paper manufacture are based on carbonates from natural sources, such as fossil sedimentary rocks (i.e., biomicrite) (Gerteiser and Laufmann, 1989), which can sometimes be recognized in the form of microfossils among the paper fibers (Bicchieri et al, 2019). It is therefore possible to speculate that the presence of cyanobacteria is due to the use of carbonatebased filler material and natural rocks, perhaps from recent sedimentation, in the manufacture -if not of the Leonardo drawing-perhaps of the cartoons supporting the drawing itself.…”
Section: Bacteriamentioning
confidence: 99%
“…It was also shown that tear index was increasing with methanol-water concentration at 60min cooking time, which shows that the tear index is proportional to methanol concentration with time. Scanning Electron Microscopy (SEM) Scanning Electron Microscopy (SEM) images has been used for the evaluations and analysis of paper structure [20,21]. The scanning image of paper prepared from hydrogen peroxide acetic acid (HPAC) bleached pulp and methanol-water pulp are shown in ( figure 5A and 5B).…”
Section: Strength Properties Of Handmade Papermentioning
confidence: 99%
“…Parchment or charta pergamena has played an important role in human history, many ancient and historical documents, manuscripts, and books being recorded on this widely used written support (Avrin 2010;Bicchieri et al, 2019). Obtained from animal hides, parchment manufacturing technique varies according to the geographical area and historical period (Avrin 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of inorganic compounds derived from the parchment manufacturing process (salts and minerals) and characterization of the black ink were carried out by using X-ray fluorescence (XRF) (Hahn et al, 2004;Wolff et al, 2012;Duran et al, 2014). Attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy (Derrick 1991;Hajji et al, 2018;Bicchieri et al, 2019;Maor, Shor, and Aizenshtat 2020) was used to obtain information on the overall state of degradation of the parchment support and investigate the presence of organic tanning agents and other nonproteinaceous materials.…”
Section: Introductionmentioning
confidence: 99%